2013
DOI: 10.1667/rr3155.1
|View full text |Cite
|
Sign up to set email alerts
|

In SituObservation of the Effects of Local Irradiation on Cytotoxic and Regulatory T Lymphocytes in Cervical Cancer Tissue

Abstract: Local radiotherapy is the major therapeutic approach to control inoperable cervical cancer. In this study, we analyzed the local immune microenvironment of cervical cancer before and after clinical radiation therapy to investigate whether tumor response due to immunomodulation. A total of 59 patients with pathologically diagnosed cervical cancers classified according to the International Federation of Obstetrics and Gynecology (FIGO) criteria were recruited. The patients were treated according to their disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…CD8 + T-cell recruitment and expansion in tumors is a good prognostic factor in many tumor types, whereas intratumoral Tregs are important promoters and stabilizers of immuno-suppressive conditions, therefore associated with poor prognosis (129). Preclinical studies on radiation-mediated effects on lymphocyte levels and profiles are somewhat contradictory, with some reports showing positive effects and others showing the opposite (130, 131). Most likely, the conflicting literature available underlines the fact that the immunological profile of cancers is tumor-type specific, and that local microenvironmental parameters such as degree of hypoxia, intratumoral pH, tumor stroma composition, and cytokine milieu are indeed key factors influencing local and systemic immune-responses after RT.…”
Section: Immune Cells and The Different Rt-regimensmentioning
confidence: 99%
“…CD8 + T-cell recruitment and expansion in tumors is a good prognostic factor in many tumor types, whereas intratumoral Tregs are important promoters and stabilizers of immuno-suppressive conditions, therefore associated with poor prognosis (129). Preclinical studies on radiation-mediated effects on lymphocyte levels and profiles are somewhat contradictory, with some reports showing positive effects and others showing the opposite (130, 131). Most likely, the conflicting literature available underlines the fact that the immunological profile of cancers is tumor-type specific, and that local microenvironmental parameters such as degree of hypoxia, intratumoral pH, tumor stroma composition, and cytokine milieu are indeed key factors influencing local and systemic immune-responses after RT.…”
Section: Immune Cells and The Different Rt-regimensmentioning
confidence: 99%
“…In our study, we also found a positive correlation between the frequency of Tc17 cell and microvessel density, supporting the proinflammatory property of IL-17–producing cells. Moreover, we also observed the correlation of Tc17 cells with Foxp3-expressing T cells in cervical cancer tissues,Foxp3-expressing T cells mediate strong immune-suppressive activity on T cell responses [39], [40]. These results indicate that Tc17 cells may promote tumor progression, but the exact function of Tc17 cells in UCC needs further investigation.…”
Section: Discussionmentioning
confidence: 64%
“…After irradiation, levels of CD4 + and CD8 + T cells decrease in the environment, while Treg cell levels remain unchanged [67]. The higher resistance of Treg cells to radiation would be due to the tumor necrosis factor receptor superfamily, member 4 (OX40) molecule [67].…”
Section: Relations Between Radiotherapy and The Tme: Clinical And Researcmentioning
confidence: 99%
“…After irradiation, levels of CD4 + and CD8 + T cells decrease in the environment, while Treg cell levels remain unchanged [67]. The higher resistance of Treg cells to radiation would be due to the tumor necrosis factor receptor superfamily, member 4 (OX40) molecule [67]. Further results in this direction indicate that overcoming the initial phase of immunosuppression could lead to a better immunogenic potential of radiotherapy [67].…”
Section: Relations Between Radiotherapy and The Tme: Clinical And Researcmentioning
confidence: 99%
See 1 more Smart Citation